Ancient landscapes of Zoara I : surveys and excavations at the Ghor as-Safi in Jordan, 1997-2018 - Politis, Konstantinos D. (New York : Routledge, 2020)
"Biblical Zoara is located in the Ghor as-Safi, precisely at the lowest place on earth. Its environmental and cultural history is therefore unique. During two decades, an archaeological project was conducted which discovered many significant finds of human occupations spanning some 12,000 years. These have been meticulously studied and the results are now presented in this comprehensive volume"--
Part I. Introduction -- Part II. The Pre-Pottery Neolithic periods -- Part III. The Bronze Age periods -- Part IV. The Late Hellenistic and Nabataean period -- Part V. The Early Byzantine period -- Part VI. The Abbasid and Ayyubid-Mamluk periods -- Part VII. The Ottoman period to modern times -- Part VII. Conclusion.
OCLC-licensed vendor bibliographic record.
Keywords: Excavations (Archaeology) -- Jordan; Human settlements -- Jordan -- History; Ghor as-Safi Site (Jordan); Jordan -- Antiquities; SOCIAL SCIENCE / Archaeology